Comparative Entrepreneurship between Western Europe and Latin America - Lopes, João (2019)
Considering the importance that entrepreneurship takes in the economies of most countries, the aim of this study was to compare two different geographical areas, studying the characteristics and variables of entrepreneurship that act as driving forces in the creation of new businesses. So, two locations from the Global Entrepreneurship Monitor (GEM) database were identified and categorized, namely Latin America (LA) and Western Europe (WE). Nine dimensions were selected, in order to test and clarify distinguishing patterns in these two locations in terms of entrepreneurial propensity.